Investigation of the Mechanical and Microstructural Properties of Welded API X70 Pipeline Steel - Ike, T. M.; Adedipe, O.; Lawal, S. A.; Abolarin, M. S.; Olugboji, O. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The mechanical properties of pipelines particularly those in marine environments are influenced by corrosion activity of seawater throughout their service lives. The degree to which these properties are influenced in seawater compared to those exposed to air needs to be better understood. In this study, the chemical composition of API X70 pipeline steel plate, microstructure and mechanical properties of the welded joints of same steel plates exposed to ambient air and seawater respectively were investigated. It was found that the base metal consisted of manganese (0.51wt% Mn), low carbon content (0.051 wt% C) and small quantities of alloying elements such as vanadium (0.021wt% V), molybdenum (0.118 wt% Mo), chromium (0.240 wt% Cr), copper (0.002 wt% Cu), and a carbon equivalent (CE IIW) of 0.38. Scanning Electron Microscope (SEM) showed that the microstructure of base metal sample has large grains formed in packets which have certain crystallographic orientation but contain submicron grains arranged in a chaotic interlocking manner. The tensile tests performed using a UNITED type universal testing machine confirmed that the yield strength of the base metal was 573.045MPa which conforms to API standard for X70 steel pipe. The manual metal arc (MMA) welding technique was applied to produce the welded joints. For the welded joints exposed to ambient air at room temperature, the yield strength was 680.624MPa while the compressive strength was 1500.2MPa, and the impact energy at -10°C was 112.68J. Air tests referred to tests conducted in the laboratory at room temperature. For the welded joints exposed to seawater for 12 weeks, the yield strength was 609.154MPa while the compressive strength was 1219.34MPa, and the impact energy at -10°C was 61.48J. The above results for air and seawater exposures were used to determine the environmental reduction factors of the two environments. Hardness tests conducted using Vickers hardness tester revealed variations in hardness across the base metal, the HAZ and the weld, with the weld having the highest average Vicker’s hardness value (223.8HV) followed by the base metal (217.3HV) and the HAZ had the least (214.5HV)